Necesidad de agregar al artículo 448 del COIP un literal, donde se incluya peritos especializados de las fuerzas armadas del Ecuador al sistema integral de investigación - Barragán Barahona, John Fabricio (2016)
The subject matter of research, is a problem that relates to the Ecuadorian reality, considering that our country has a large space of territorial waters, this being an important step for the global elites want drug transit through our maritime areas. Ecuadorian society is immersed in a capitalist system, whose function and philosophy consider a potential tool for development, but the problem lies in the misrepresentation of the social and economic order that derives from the use of property, as in the case of my research that goes beyond the territorial part but entering the territorial part for being a land of peace, where they raised to our territory is free of drugs eradicated positively to this evil of society itself. The state has tried to fully regulate certain standards evidenced in the law, as is the case of INTEGRAL ORGANIC PENAL CODE (COIP), but it has some weaknesses denoted in which it has been possible to demonstrate the support that has the Armed Forces engaging in any field three fields Land, Naval and Air, these shortcomings are in the investigative system, specifically the Navy performs in capturing smuggling, drug, fishing not allowed, among others, to help investigate these ancillary crimes such actions in investigations of aquatic crimes. In pretrial and procedural matters criminal, the prosecutor is the one who organizes and conducts specialized research system in which the Navy is not taken as part of the research, this being who with his media gives birth to crime produced in the aquatic spaces. It is noteworthy that for this the Navy is a branch of the armed forces in which he characterized as the custodian of the territorial sea, assuming the role of maritime police, it is in this way that is part of the Constitution of the Republic of Ecuador, and stipulated their actions on the agenda of the defense policy, this whole context is not provided in the investigation in the second section of my research so it is necessary that it be expressed tacitly to be part as an auxiliary body for the prosecution in the processes of aquatic crimes